Acute Decompensated Heart Failure and the Kidney: Physiological, Histological and Transcriptomic Responses to Development and Recovery - Miriam T. Rademaker (Wiley, 2021)
BACKGROUND Acute decompensated heart failure (ADHF) is associated with deterioration in renal function—an important risk factor for poor outcomes. Whether ADHF results in permanent kidney damage/dysfunction is unknown. METHODS AND RESULTS We investigated for the first time the renal responses to the development of, and recovery from, ADHF using an ovine model. ADHF development induced pronounced hemodynamic changes, neurohormonal activation, and decline in renal function, including decreased urine, sodium and urea excretion, and creatinine clearance. Following ADHF recovery (25 days), creatinine clearance reductions persisted. Kidney biopsies taken during ADHF and following recovery showed widespread mesangial cell prominence, early mild acute tubular injury, and medullary/interstitial fibrosis. Renal transcriptomes identified altered expression of 270 genes following ADHF development and 631 genes following recovery. A total of 47 genes remained altered post‐recovery. Pathway analysis suggested gene expression changes, driven by a network of inflammatory cytokines centered on IL‐1β (interleukin 1β), lead to repression of reno‐protective eNOS (endothelial nitric oxide synthase) signaling during ADHF development, and following recovery, activation of glomerulosclerosis and reno‐protective pathways and repression of proinflammatory/fibrotic pathways. A total of 31 dysregulated genes encoding proteins detectable in urine, serum, and plasma identified potential candidate markers for kidney repair (including CNGA3 [cyclic nucleotide gated channel subunit alpha 3] and OIT3 [oncoprotein induced transcript 3]) or long‐term renal impairment in ADHF (including ACTG2 [actin gamma 2, smooth muscle] and ANGPTL4 [angiopoietin like 4]). CONCLUSIONS In an ovine model, we provide the first direct evidence that an episode of ADHF leads to an immediate decline in kidney function that failed to fully resolve after ≈4 weeks and is associated with persistent functional/structural kidney injury. We identified molecular pathways underlying kidney injury and repair in ADHF and highlighted 31 novel candidate biomarkers for acute kidney injury in this setting.